Adaptation and Psychometric Validation of The Peer Support Questionnaire for Indonesian University Students - Nindy Amita; Hazalizah Hamzah (Psyche 165 Journal, 2026)
University students are in a developmental phase characterized by increasingly complex academic and social demands, making peer support a crucial factor in their adaptation and psychological well-being. This study aimed to adapt and test the psychometric properties of the Indonesian version of the Peer Support Questionnaire (PSQ) from Alaei and Hosseinnezhad (2020) among university students. The study employed a quantitative, cross-sectional design and included 530 students. The instrument adaptation process was based on a cross-cultural adaptation framework, and construct validity was assessed using Confirmatory Factor Analysis (CFA). The analysis showed that all items had adequate standardized factor loadings (0.70–0.84), and the five-dimensional factor structure demonstrated good model fit across various fit indices. Model fit evaluation showed good results (CFI = 0.959; TLI = 0.953; RMSEA = 0.059; SRMR = 0.030). In addition, the results of the convergent validity and construct reliability tests showed that the AVE values ranged from 0.56 to 0.68, and the Composite Reliability ranged from 0.83 to 0.90. These findings indicate that the Indonesian version of the PSQ meets the recommended psychometric criteria and can be considered a valid and reliable instrument for assessing peer support among university students in Indonesia